2021
DOI: 10.3390/molecules26051464
|View full text |Cite
|
Sign up to set email alerts
|

Bioguided Fractionation of Local Plants against Matrix Metalloproteinase9 and Its Cytotoxicity against Breast Cancer Cell Models: In Silico and In Vitro Study (Part II)

Abstract: In our previous work, the partitions (1 mg/mL) of Ageratum conyzoides (AC) aerial parts and Ixora coccinea (IC) leaves showed inhibitions of 94% and 96%, respectively, whereas their fractions showed IC50 43 and 116 µg/mL, respectively, toward Matrix Metalloproteinase9 (MMP9), an enzyme that catalyzes a proteolysis of extracellular matrix. In this present study, we performed IC50 determinations for AC n-hexane, IC n-hexane, and IC ethylacetate partitions, followed by the cytotoxicity study of individual partiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…precocene I, β-sitosterol, precocene II, 6-vinyl-7-methoxy-2,2-dimethyl chromene (VMDC), stigmasterol, polymethoxyflavone, pyrrolizidine, neophytadiene, phytol, and caryophyllene isolated from ACE have been used to screen their potential application against various drug targets (e.g., MMP-9, p53, cox-2, α -amylase, etc.) for various diseases like malaria, diabetes, breast cancer and cervical cancer [ 75 78 ]. Recently, key secondary metabolites (e.g., Kaempferol, Quercetin, etc.)…”
Section: Evaluation Of Traditional Medicinal Uses By Molecular Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…precocene I, β-sitosterol, precocene II, 6-vinyl-7-methoxy-2,2-dimethyl chromene (VMDC), stigmasterol, polymethoxyflavone, pyrrolizidine, neophytadiene, phytol, and caryophyllene isolated from ACE have been used to screen their potential application against various drug targets (e.g., MMP-9, p53, cox-2, α -amylase, etc.) for various diseases like malaria, diabetes, breast cancer and cervical cancer [ 75 78 ]. Recently, key secondary metabolites (e.g., Kaempferol, Quercetin, etc.)…”
Section: Evaluation Of Traditional Medicinal Uses By Molecular Toolsmentioning
confidence: 99%
“…Also, the level of MMP-9 expression is the key indicator of triple-negative breast cancer disease diagnosis. Recently, Hariono et al [ 78 ] used the n -hexane fraction of ACE to assess its inhibitory potential against MMP-9. The compound oxytetracycline (OTC) isolated from n -hexane fraction had a potent inhibitory effect against MMP-9 with IC 50 value of 246.1 µg/ mL.…”
Section: Evaluation Of Traditional Medicinal Uses By Molecular Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Furthermore, the natural product is thought to have significant cytotoxic potential. 11 This study was aimed at investigating the potential of S. quadrifida leaf extract as a cytotoxic agent in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported some local plants demonstrating significant inhibition toward matrix metalloproteinase-9 (MMP-9), a proteolytic enzyme having roles in extracellular matrix (ECM) degradation which facilitates in-cell migration related to cancer metastasis [34] , [35] . Since both MMP-9 and 3CLpro are proteolytic enzymes, this prompts us to explore the probability of these plants to be the 3CLpro inhibitor as well.…”
Section: Introductionmentioning
confidence: 99%